Agroecology Now! Transformations Towards More Just and Sustainable Food Systems - Anderson, Colin Ray; Bruil, Janneke; Chappell, M. Jahi; Kiss, Csilla; Pimbert, Michel Patrick (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book develops a framework for advancing agroecology transformations focusing on power, politics and governance. It explores the potential of agroecology as a sustainable and socially just alternative to today's dominant food regime. Agroecology is an ecological approach to farming that addresses climate change and biodiversity loss while contributing to the Sustainable Development Goals. Agroecology transformations represent a challenge to the power of corporations in controlling food system and a rejection of the industrial food systems that are at the root of many social and ecological ills. In this book the authors analyse the conditions that enable and disable agroecology's potential and present six 'domains of transformation' where it comes into conflict with the dominant food system. They argue that food sovereignty, community-self organization and a shift to bottom-up governance are critical for the transformation to a socially just and ecologically viable foodsystem. This book will be a valuable resource to researchers, students, policy makers and professionals across multidisciplinary areas including in the fields of food politics, international development, sustainability and resilience. Colin Ray Anderson is Associate Professor at the Centre for Agroecology, Water and Resilience, Coventry University, UK. His research focuses on food systems, sustainability transitions, social movement organizing and knowledge mobilization. Janneke Bruil is a co-founder, facilitator and researcher at Cultivate!, an international collective that works with social movements to advance healthy and just food systems rooted in agroecology. She is also an active member of Voedsel Anders, the Dutch food sovereignty platform. M. Jahi Chappell is the Executive Director of SAAFON (the Southeastern African-American Farmers' Organic Network), the author of the award-winning book Beginning to End Hunger, and Honorary Research Fellow at the Centre for Agroecology, Water, and Resilience, UK. Csilla Kiss works as International Research Engagement and Liaison Officer at the Centre for Agroecology, Water and Resilience at Coventry University, UK. She supports collaborative research across the world on socially just and ecologically sustainable food systems. Michel Patrick Pimbert is Professor of Agroecology and Food Politics as well as Director of the Centre for Agroecology, Water and Resilience at Coventry University, UK. .